Parthenium hysterophorus L.: Highly allergic invasive alien plant growing tremendously in Nepal - Adhikari, Bhaskar; Tirwari, Sagendra (Botanica Orientalis: Journal of Plant Science, 2007)
Botanica Orientalis Vol.4(1) 2004. p.36-37